PEMBAGIAN WARISAN ANAK TIRI DITINJAU DARI HUKUM ISLAM (Studi kasus Desa Bumi Mulya, Logas Tanah Darat, Kabupaten Kuantan Singingi) - Krismayanti Krismayanti; Zulkifli Zulkifli (Jurnal Integrasi Ilmu Syariah (Jisrah), 2022)
This study examines the study of Islamic law on the practice of dividing the inheritance of stepchildren in Bumi Mulya village, Logas Tanah Darat sub-district, Kuantan Singingi Regency, Riau Province. The problem is that some of the people of Bumi Mulya village give inheritance to their stepchildren. From these problems, the question arises what are the factors that some of the people of Bumi Mulya village make and give stepchildren as people who are entitled to receive inheritance and how is the system for dividing the inheritance of stepchildren in Bumi Mulya village. This research is a type of field research. Sources of data in this research obtained through observation and interviews. data is processed by triangulation. Then it is narrated descriptively. The results of this study are the factors that some people make stepchildren as people who are entitled to inherit property are: stepchildren are part of the family component, to minimize disputes, to repay children's services in their participation in looking for property and caring for parents, stepchild inheritance division system The distribution carried out by the Bumi Mulya village community is by way of deliberation and grants.